Cloud service for authentication of a person based on their electrocardiogram - Luhovskyi, Yu.O. (Проблеми програмування, 2022)
Telemedicine grows faster with each year. In scope of it new technologies have been created to solve information communication problems. One of them is distance monitoring which requires electrocardiogram analysis. In this case it is important to confirm that the transferred electrocardiogram through information channels belongs to the patient. Researchers from different countries work on this problem. They suggest different methods of authentication by electrocardiogram. The goal of this work is to suggest a prototype of a service that could be used to authenticate electrocardiograms. The paper describes which algorithms have been used to build authentication technology and how it was implemented. There is a short history of built applications. It shows their structures and the purpose. The recently developed system is a prototype to authentication service. It performs registration of new electrocardiograms which is the most time consuming process in authentication. The paper describes the architecture of the system and shows the result of executed experiments. The results show that there is a performance issue with the machine learning library ML.NET. When a lot of cores are allocated to one machine learning instance the overheads highly decrease the overall experiment time. These experiments confirmed Amdahl’s law. Nevertheless, an architecture was found where experiments took the least time for execution. Knowing the issue with the machine learning library, a new architecture setup was suggested and will be implemented in future works. Besides, attention is paid on how developed service should help researchers to improve the technology. The main idea of the system is using one service for developing and testing the technology. That means we can be sure that the cloud service that runs on production would behave the same as in the research phase. Телемедицина з кожним роком пришвидшує свій розвиток. Відбувається це за рахунок винайдення нових технологій, що розвивають комунікацію та роботу з даними. Одним із напрямків, в телемедицині є дистанційний моніторинг, задачею якого є постійно контролювати стан пацієнта. Це здійснюється перевіркою різних показників, в тому числі, йі електрокардіограми. Важливо, щоб надіслана кардіограма належала саме пацієнтові на моніторингу. Для цього розробляється технологія автентифікації по електрокардіограмі. Дослідники з різних країн працюють над цим питанням використовуючи підходи, що можуть сильно відрізнятись. В цій роботі описується прототип хмарного сервісу по автентифікації. Описуються алгоритми, що використовувались для побудови технології автентифікації та додатків, що реалізують цю технологію. Показуються послідовні розробки додатків та описуються їх задачі. Останній розроблений додаток - це хмарний сервіс, побудований на мікросервісах, що виконує реєстрацію електрокардіограм. Це є найбільш витратна щодо часу операція автентифікації. Приводиться архітектура сервісу та результати експериментів. По результатах помітно, що є проблеми з машинним навчанням, а саме бібліотекою ML.NET. Коли виділяється багато ядер для одного екземпляра мікросервіса, що навчає нейромережі, виникають накладні витрати на розпаралелювання, що сильно впливає на продуктивність. Це підтверджує закон Амдала. За наявної архітектури була знайдена конфігурація, при якій час на проведення експериментів був найменшим. Враховуючи проблему з накладними витратами нова архітектура була запропонована для подальших досліджень. Розглядається, як розроблена архітектура повинна допомогти в розвитку технології. Ідея системи полягає у використанні одного і того ж сервісу для досліджень і в промисловому використанні. Це дасть гарантію, що промисловий сервіс буде поводитись так само як і при дослідженні.